No cataclysmic variables missing: higher merger rate brings into agreement observed and predicted space densities. Issue 4 (4th June 2018) - Belloni, Diogo; Schreiber, Matthias R; Zorotovic, Mónica; Iłkiewicz, Krystian; Hurley, Jarrod R; Giersz, Mirek; Lagos, Felipe
ABSTRACT: The predicted and observed space density of cataclysmic variables (CVs) has been for a long time discrepant by at least an order of magnitude. The standard model of CV evolution predicts that the vast majority of CVs should be period bouncers, whose space density has been recently measured to be ρ ≲ 2 × 10 −5 pc −3 . We performed population synthesis of CVs using an updated version of the Binary Stellar Evolution (bse ) code for single and binary star evolution. We find that the recently suggested empirical prescription of consequential angular momentum loss (CAML) brings into agreement predicted and observed space densities of CVs and period bouncers. To progress with our understanding of CV evolution it is crucial to understand the physical mechanism behind empirical CAML. Our changes to the bse code are also provided in details, which will allow the community to accurately model mass transfer in interacting binaries in which degenerate objects accrete from low-mass main-sequence donor stars.